Identifying gene targets for brain-related traits using transcriptomic and methylomic data from blood - Ting Qi (Nature Portfolio, 2018)
To comprehend the genetic regulatory mechanisms underlying brain-related traits in humans, Qi et al. estimate the correlation of expression and DNA methylation QTL effects in cis between blood and brain and show that using blood eQTL/mQTL data of large sample size  can increase power in gene discovery for brain-related traits and diseases.